La relation aux traditions et aux modes de socialisation traditionnels des Églises évangéliques Born Again aux Philippines - Jérémy Ianni (Cahiers d'Études du Religieux- Recherches Interdisciplinaires, 2023)
Although the Born Again Churches in the Philippines call into question certain traditions, they are popular as more and more people join them. Based on a field survey and data collected in the network of the Council of Evangelical Churches in the Philippines, the author shows that, although these churches tend to question certain traditions, they nevertheless rely on traditional modes of socialization to develop. Between the collective self – the figure of the kapwa – and unity, the organization of religious charismatic power in the Philippines is based on traditional socializations.